2015
DOI: 10.1073/pnas.1409952112
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo characterization of chronic traumatic encephalopathy using [F-18]FDDNP PET brain imaging

Abstract: Chronic traumatic encephalopathy (CTE) is an acquired primary tauopathy with a variety of cognitive, behavioral, and motor symptoms linked to cumulative brain damage sustained from single, episodic, or repetitive traumatic brain injury (TBI). No definitive clinical diagnosis for this condition exists. In this work, we used [F-18]FDDNP PET to detect brain patterns of neuropathology distribution in retired professional American football players with suspected CTE (n = 14) and compared results with those of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 59 publications
7
118
1
1
Order By: Relevance
“…129 The study of the 5 players by Small et al 129 was followed by a larger study involving 18 F-FDDNP PET imaging of 14 retired professional football players (5 of whom were included in the earlier study) with suspected CTE and 24 patients with Alzheimer's dementia. 7 In vivo imaging suggests that tau deposition in the football player group was consistent with the postmortem pattern of confirmed CTE cases previously described by McKee et al and Omalu et al Both methods showed involvement of subcortical structures, the medial temporal lobe, and the frontal cortex. In addition, the FDDNP signal in the suspected CTE group was distinct from that of the AD group, which suggests that this tracer can be specific for CTE.…”
supporting
confidence: 85%
“…129 The study of the 5 players by Small et al 129 was followed by a larger study involving 18 F-FDDNP PET imaging of 14 retired professional football players (5 of whom were included in the earlier study) with suspected CTE and 24 patients with Alzheimer's dementia. 7 In vivo imaging suggests that tau deposition in the football player group was consistent with the postmortem pattern of confirmed CTE cases previously described by McKee et al and Omalu et al Both methods showed involvement of subcortical structures, the medial temporal lobe, and the frontal cortex. In addition, the FDDNP signal in the suspected CTE group was distinct from that of the AD group, which suggests that this tracer can be specific for CTE.…”
supporting
confidence: 85%
“…The discrepancy between the current studies' findings and those of Nesilus and colleagues are unclear, warranting future research on the potential dysregulation of plasma T-tau chronically after brain injury. Understanding the relationship between peripheral blood T-tau levels and axonal injury or the accumulation of tau in the brain is important, as peripheral tau has been linked to chronic neurodegenerative disorders such as chronic traumatic encephalopathy and Alzheimer's disease (42,47,(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging has been a particularly powerful application, with positron emission tomography (PET) scans using 2-(1-{6-[ (2-[F-18] fluoroethyl) (methyl)amino]-2-naphthyl}ethylidene)malononitrile (FDDNP) revealing high signals in the brainstem, amygdala, and orbital frontal cortex. 7,8 These same brain region show high tau accumulation in autopsy cases of CTE. Diffusion tensor imaging has also suggested abnormalities in fractional anisotropy in patients with depression and anxiety after TBI.…”
Section: Introductionmentioning
confidence: 84%